2011
DOI: 10.3233/nre-2011-0639
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of upper limb dexterity in patients more than 1 year after stroke: Frequency, clinical correlates and predictors

Abstract: Objective: The objectives of this study are to establish frequency, clinical correlates and predictors of upper limb dexterity in patients who have survived 1 year or more after a stroke. Design: Cross-sectional study. Setting: Outpatient clinic of a tertiary rehabilitation centre. Participants: One hundred and forty patients who were more than a year after stroke onset. Interventions: Nil. Main outcome measures: Motor Assessment Scale (MAS) for measurement of upper limb dexterity, Ashworth Scale for spasticit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 18 publications
1
47
0
2
Order By: Relevance
“…Studies have shown that while 82% of patients with stroke ambulate independently, 1 only 5% to 34% achieve full upper limb function. 2,3 These differences in recovery of upper and lower limb are thought to be partly due to less time spent in rehabilitating the upper limb 46 and decreased spontaneous use of the affected upper limb, both of which contribute to learned non-use. 7 Once discharged from inpatient and outpatient rehabilitation services, the gap between upper and lower limb function often widens because patients’ do not know how to maximize use of their affected hand in their own environment, and options for continued therapy in a formal setting are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that while 82% of patients with stroke ambulate independently, 1 only 5% to 34% achieve full upper limb function. 2,3 These differences in recovery of upper and lower limb are thought to be partly due to less time spent in rehabilitating the upper limb 46 and decreased spontaneous use of the affected upper limb, both of which contribute to learned non-use. 7 Once discharged from inpatient and outpatient rehabilitation services, the gap between upper and lower limb function often widens because patients’ do not know how to maximize use of their affected hand in their own environment, and options for continued therapy in a formal setting are limited.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of hand motor impairment and its treatment after stroke has also been reviewed (Raghavan, 2007), as well as treatment’s intensity (Cooke et al, 2010). Whatever the strategy used to re-train precision grip, a large cohort study shows that the likelihood to regain some dexterity is strongly linked to the presence of early voluntary extension of the fingers and abduction of the shoulder (Nijland et al, 2010; Kong et al, 2011). …”
Section: Implications For Rehabilitationmentioning
confidence: 99%
“…Among these survivors, a large proportion (46% to 95%) remains symptomatic six months after the ischemic stroke event [2]. Loss of arm function adversely affects quality of life [3], and functional motor recovery in affected upper extremities in patients with hemiplegia is the primary goal of physical therapists [4].…”
Section: Introductionmentioning
confidence: 99%